Determination of correlation level and process capability of a manufacturing process using control charts. (2017) - Prajapati, D.R.
Statistical process control is an industry-based methodology for measuring and controlling quality during the manufacturing process. The case study presented in this paper deals with the determination of process capability ratio (PCR), process capability index (Cpk ) and level of correlation for a 'drive shaft run outs' of the manufacturing industry. Data have been taken from the manufacturing process and the -X and R control charts have been plotted to find whether the processes are with-in or out of statistical control. Process capability analysis has been done to find the effectiveness of the processes. It is found that the 36.02% of drive shaft run outs is beyond the control, which is really a higher rejection level and major concern for the industry. The samples of 'drive shaft run outs' are taken from a manufacturing industry located in India and estimated the level of correlation among the observations. The level of correlation among the observations of the 'drive shaft run outs' has been computed and matched with the suggested optimal schemes of Shewhart -X chart for sample size (n) of four. The presented case study shows the level of correlation of 0.50.